Gastric Outlet Obstruction as the Initial Presentation of Upper Tract Urothelial Carcinoma. (19th October 2020) - Andersen, Karl; Burroughs, Sarah; Munis, Assad; Hoff, Ryan T.; Shapiro, Alan
Abstract : GOO is often the first sign of advanced upper gastrointestinal neoplasms. The most common neoplasms associated with GOO include gastric, pancreatic, and biliary tract cancers. Urinary tract urothelial carcinoma has been a rarely documented cause of GOO.